Development of a Magneto-Optical Trap System of Francium Atoms for the Electron Electric-Dipole-Moment Search. (February 2016) - Harada, K; Aoki, T; Kato, K; Kawamura, H; Inoue, T; Aoki, T; Uchiyama, A; Sakamoto, K; Ito, S; Itoh, M; Hayamizu, T; Hatakeyama, A; et al.
Abstract: The finite value of an electron electric dipole moment (eEDM) provides the direct evidence for the violation of time reversal symmetry. Fr atoms, whose enhancement factor is 895, trapped by laser cooling and trapping techniques are one of the strongest candidates for measuring the eEDM. We are constructing a beamline for measuring the eEDM using laser- cooled Fr atoms at the Cyclotron and Radioisotope Center. We have developed laser light sources including the frequency stabilization system and a magneto-optical trap system for Fr atoms. As the Fr production requires the cyclotron operation, we also use Rb atoms whose chemical properties are similar to those of the Fr atoms. Thus, the Rb beam is utilized for optimizing the operation parameters of the entire apparatus. We have also developed the laser light sources for Rb atoms and observed the beat signal for frequency stabilization of the source using the frequency offset locking method.